Photodynamic therapy (PDT) as adjuvant treatment to brachytherapy for amelanotic choroidal melanoma. Issue 2 (March 2023) - Pagliara, Monica Maria; Sammarco, Maria Grazia; Caputo, Carmela Grazia; Pafundi, Pia Clara; Giannuzzi, Federico; Fionda, Bruno; Scupola, Andrea; Tagliaferri, Luca; Rizzo, Stanislao; Blasi, Maria Antonietta
Purpose: To evaluate the effect of photodynamic therapy (PDT) as adjuvant treatment, after brachytherapy, in posterior amelanotic choroidal melanomas. Methods: Six patients with posterior amelanotic choroidal melanoma underwent brachytherapy treatment. Tumour response was assessed by fundus examination, fundus photography and A-B scan ultrasonography. The residual tumours were treated with adjuvant PDT performed with infusion of verteporfin intravenously at 6 mg/m 2 body surface area. Five minutes after infusion, a 689 nm laser was applied with a light dose of 100 J/cm 2 over an interval of 166 s. Results: At a median follow-up after brachytherapy of 17.5 months (IQR 16.2–22.5, range 5–42 months), tumours showed a partial reduction of tumour thickness (22.5% as compared to baseline value) and persistent low internal reflectivity at A-B scan ultrasonography. Supplementary photodynamic treatment resulted in complete resolution of the lesion with marked decrease of elevation . Mean decrease in thickness after PDT was 49.9% with respect to previous brachytherapy treatment 22.5% (p = 0.007). The results was achieved within a median period of 4 months (range 2–4 months) after PDT, and there has been no recurrence after a median follow-up of 84.7 months ± 18.7 (range 59 to 107 months). Conclusion: Combined treatment of brachytherapy and adjuvant PDT in amelanotic uveal melanoma seems to be favourable with regard to complete and rapid tumour regression.